Degradation of dead cladoceran zooplankton and their contribution to organic carbon cycling in stratified lakes: field observation and model prediction. (6th May 2022) - Tolomeev, Aleksandr P; Dubovskaya, Olga P; Kirillin, Georgiy; Buseva, Zhanna; Kolmakova, Olesya V; Grossart, Hans-Peter; Tang, Kam W; Gladyshev, Michail I
Abstract: The contribution of dead zooplankton biomass to carbon cycle in aquatic ecosystems is practically unknown. Using abundance data of zooplankton in water column and dead zooplankton in sediment traps in Lake Stechlin, an ecological-mathematical model was developed to simulate the abundance and sinking of zooplankton carcasses and predict the related release of labile organic matter (LOM) into the water column. We found species-specific differences in mortality rate of the dominant zooplankton: Daphnia cucullata, Bosmina coregoni and Diaphanosoma brachyurum (0.008, 0.129 and 0.020 day −1, respectively) and differences in their carcass sinking velocities in metalimnion (and hypolimnion): 2.1 (7.64), 14.0 (19.5) and 1.1 (5.9) m day −1, respectively. Our model simulating formation and degradation processes of dead zooplankton predicted a bimodal distribution of the released LOM: epilimnic and metalimnic peaks of comparable intensity, ca. 1 mg DW m −3 day −1 . Maximum degradation of carcasses up to ca. 1.7 mg DW m −3 day −1 occurred in the density gradient zone of metalimnion. LOM released from zooplankton carcasses into the surrounding water may stimulate microbial activity and facilitate microbial degradation of more refractory organic matter; therefore, dead zooplankton are expected to be an integral part of water column carbon source/sink dynamics in stratified lakes.